Noise Level in Kirkuk University Library - Rabab Shakor Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The study was conducted at Kirkuk University Library to investigate the noise levels. The researchers collected noise level readings at specific time points throughout the day, including morning, mid-day, and afternoon. The purpose of the study was to analyze the variations in noise levels and assess their impact. The findings of the study indicate that the average noise levels measured during the three-time points consistently exceeded the guideline limit set by the World Health Organization (WHO). The study provides valuable insights into the noise levels at Kirkuk University Library and emphasizes the need for interventions to address excessive noise. Implementing measures to reduce noise disturbances and promote a quieter environment can significantly enhance the library experience for users, allowing for improved concentration, better learning outcomes, and overall satisfaction. Taking proactive measures to address excessive noise levels in the Kirkuk University Library is crucial for creating an optimal learning environment. Reducing noise disturbances not only improves students' ability to understand and absorb information but also reduces stress levels and promotes calmness in the library.